Minimization of 1/fn phase noise in liquid crystal masks for reliable femtosecond pulse shaping - Brühl, Elisabeth; Buckup, Tiago; Motzkus, Marcus (Optics express, 2017)
Liquid-crystal spatial light modulators (LCM) are a common tool to tailor femtosecond laser pulses. The phase stability of 1 kHz, sub-20 fs visible shaped and unshaped pulses are investigated. Our results show that the spectral phase after the LCM varies from pulse to pulse leading to strong deviations from the predicted pulse shapes. This phase instability is generated only by LCM and is strongly temperature dependent. Based on the experimental data, a numerical model for the phase was developed that takes the temperature-dependent phase instability as well as pixel coupling across the LCM into account. Phase stability after the LCM can be improved by an order of magnitude by combining the control the temperature of the LCM and by using rapid-scan averaging. Reliable pulse shapes on a pulse-to-pulse basis are crucial, especially in coherent control experiments, where small differences between pulse shape are important.
Im Titel ist der Buchstabe "n" bei "1/fn" hochgestellt
Gesehen am 10.09.2017